2019
DOI: 10.1111/cns.13093
|View full text |Cite
|
Sign up to set email alerts
|

Batroxobin in combination with anticoagulation may promote venous sinus recanalization in cerebral venous thrombosis: A real‐world experience

Abstract: Summary Aims The objective of this study was to evaluate cerebral venous recanalization with magnetic resonance black‐blood thrombus imaging (MRBTI) in patients with cerebral venous thrombosis (CVT) who underwent batroxobin treatment in combination with anticoagulation. Methods A total of 31 CVT patients were enrolled in this real‐world registry study. The patients were divided into batroxobin (n = 21) and control groups (n = 10). In addition to the same st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Of note, our previous work ever highlighted the adjunctive contribution of batroxobin to the dissolution of CVT, which enabled to accelerate thrombolysis and result in rapid recanalization. 34 , 35 Although our current study waived to explore the responses of both CVT and IJVS‐CVT to batroxobin, a well‐designed clinical trial regarding batroxobin efficacy in treating CVT and IJVS‐CVT is underway, and will draw a conclusion in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, our previous work ever highlighted the adjunctive contribution of batroxobin to the dissolution of CVT, which enabled to accelerate thrombolysis and result in rapid recanalization. 34 , 35 Although our current study waived to explore the responses of both CVT and IJVS‐CVT to batroxobin, a well‐designed clinical trial regarding batroxobin efficacy in treating CVT and IJVS‐CVT is underway, and will draw a conclusion in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term standardized anticoagulation is widely accepted as the first-line strategy for CVST. However, our previous study indicated that multitherapy of batroxobin and anticoagulation treatments could reduce the restenosis rate and accelerate cerebral venous recanalization compared with anticoagulation monotherapy in patients with CVST ( 14 , 15 ). In the clinical setting, we found that some patients with CCVT still experienced symptoms despite long-term anticoagulation treatment.…”
Section: Discussionmentioning
confidence: 95%
“…Nevertheless, its utility for CCVT diagnosis has not yet been confirmed. With regard to CVST treatment, we previously found that batroxobin, combined with anticoagulation, can safely and effectively improve clinical outcomes and reduce restenosis in patients with acute CVST ( 14 , 15 ). To evaluate the clinical applications of this novel imaging sequence in diagnosing CCVT, and to evaluate the efficacy of batroxobin for treating CCVT, we conducted a cohort study of Chinese patients with CCVT.…”
Section: Introductionmentioning
confidence: 99%
“…Ding et al analyzed the safety and efficacy of batroxobin in combination with anticoagulants on CVT and found a higher recanalization rate in the batroxobin group compared with the control group, especially in CVT patients with a high level of fibrinogen. Severe hemorrhagic events were not observed [ 92 , 93 ].…”
Section: Cerebral Venous Thrombosismentioning
confidence: 99%